IMPLEMENTASI PROGRAM KARTU INDONESIA PINTAR (KIP) BERDASARKAN BASIS NILAI KEADILAN DALAM KEBIJAKAN SOSIAL - Arie Surya Gutama; Muhammad Fedryansyah; Eva Nuriyah (Jurnal Penelitian dan Pengabdian Kepada Masyarakat (JPPM), 2021)
Indonesia Pintar (PIP) program is a government program that aims to provide educational cash assistance aimed at vulnerable elementary, junior high, and high school students after 6-21 years of economic inequality. PIP recipients will receive a Smart Indonesia Card (KIP) which is given as an identity marker as the beneficiary of the PIP program. This research aims to find out the implementation of PIP in various regions in Indonesia, know the obstacles during the program and identify this PIP as a social policy. The results showed that PIP as a social policy has fulfilled equity value as one of the important instruments of social policy, but the implementation of PIP program that receives PIP assistance has not been fully optimal when in the field. Not all children who are eligible to receive assistance in Indonesia can enjoy the educational assistance.